Students’ Spatial and Visual Literacies - Yun Fan; Xiang Xia (FORMakademisk, 2023)
This research examines whether different disciplinary backgrounds influence the development of design students’ visual literacy. A compulsory first-year course in Chinese design degree programmes was selected for this research, as such a course is designed to develop students’ spatial literacy and visual expression during the discovery design process phase and to facilitate the development of students’ cognitive skills in defining and solving problems. An analysis of 16 students’ assignments from eight universities indicates that students’ disciplinary backgrounds play an important role in the development of their cognition performance related to visual literacy. The results indicate that the disciplinary subject background (i.e. arts or engineering) is an important factor affecting the development of students’ design literacy, specifically their spatial visual cognitive and problem-solving skills.